ChemInform Abstract: An Efficient Organocatalytic Enantioselective Synthesis of Spironitrocyclopropanes. Issue 21 (2nd May 2013) - Das, Utpal; Tsai, Yi‐Ling; Lin, Wenwei
Abstract starting from 2‐arylidene‐1, 3‐indanediones (I) and corresponding bromonitroalkanes